Vaccine Candidate Against COVID-19 Based on Structurally Modified Plant Virus as an Adjuvant - Kovalenko, Angelina O.; Ryabchevskaya, Ekaterina M.; Evtushenko, Ekaterina A.; Manukhova, Tatiana I.; Kondakova, Olga A.; Ivanov, Peter A.; Arkhipenko, Marina V.; Gushchin, Vladimir A.; Nikitin, Nikolai A.; Karpova, Olga V. (Frontiers in Microbiology, 2022)
A recombinant vaccine candidate has been developed based on the major coronaviruses’ antigen (S protein) fragments and a novel adjuvant—spherical particles (SPs) formed during tobacco mosaic virus thermal remodeling. The receptor-binding domain and the highly conserved antigenic fragments of the S2 protein subunit were chosen for the design of recombinant coronavirus antigens. The set of three antigens (Co1, CoF, and PE) was developed and used to create a vaccine candidate composed of antigens and SPs (SPs + 3AG). Recognition of SPs + 3AG compositions by commercially available antibodies against spike proteins of SARS-CoV and SARS-CoV-2 was confirmed. The immunogenicity testing of these compositions in a mouse model showed that SPs improved immune response to the CoF and PE antigens. Total IgG titers against both proteins were 9–16 times higher than those to SPs. Neutralizing activity against SARS-CoV-2 in serum samples collected from hamsters immunized with the SPs + 3AG was demonstrated.